Effect of boiling water soaking on the mechanical properties and durability of nanoclay-enhanced bamboo and glass fiber epoxy composites - Syed Mansoor Ahmad; M. C. Gowrishankar; Manjunath Shettar (Scientific Reports)
Abstract Fiber-reinforced polymer composites are subjected to harsh environmental conditions over the course of their designed lifespan. Studying the aging process of fiber-reinforced polymer composites exposed to boiling water is critical for improving their durability. This study uses a hand lay-up technique to fabricate composites from glass fiber, bamboo fiber, nanoclay, and epoxy. Tensile and flexural tests are conducted following ASTM standards. The % of water uptake of the boiling water-soaked specimens is measured, and the performance of the dry composites is compared with those of boiling water-soaked composites. The results show that boiling water-soaking conditions have an adverse impact on all the composites. Boiling water-soaked epoxy samples show a reduction in tensile properties by 25 and 30% and flexural properties by 18 and 22% under processes 1 and 2 of boiling water soaking, respectively, compared to dry ones. Meanwhile, for fiber-reinforced composites, the tensile properties decrease by 19 and 27%, and the flexural properties decline by 12 and 20% under processes 1 and 2 of boiling soaking, respectively. However, incorporating nanoclay enhances the tensile and flexural properties of the epoxy and the composites by 5 to 7% and 10 to 12%, respectively. The water absorption rate and the impact of boiling water-soaking on composite strength decrease with the addition of nanoclay. Additionally, nanoclay reduces the percentage of reduction in tensile properties by 17 and 26% and in flexural properties by 11 and 18% under processes 1 and 2 of boiling soaking, respectively. SEM analysis of the fracture surfaces reveals the causes of specimen failure under tensile load, with distinct differences between dry and boiling water-soaked specimens.